2013
DOI: 10.20396/rbi.v12i2.8649066
|View full text |Cite
|
Sign up to set email alerts
|

Características estruturais da rede colaborativa de pesquisa de milho no contexto das ciências agrárias

Abstract: Os autores agradecem aos pareceristas, que empenharam seu tempo e expertise para ajudar a melhorar este trabalho. Muito obrigado. Essa pesquisa teve o apoio do Prospeq/Cefet-MG. R O objetivo deste trabalho é descrever a estrutura formada pelas interações entre as entidades de pesquisadores engajadas na criação de tecnologias aplicáveis ao milho em comparação com àqueles arranjos voltados para o café e a soja, três das culturas mais relevantes para o Brasil. Para tanto, foram privilegiadas a Análise de Redes So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Araújo et al [4] investigated the collaborative public networks of corn research in Brazil between 2006 and 2010, and found close ties between the institutions involved in the enhancement of cultivars and those working on the development of technology for the improvement of productivity (Figure 1). Research efforts are concentrated in Southeast Brazil, where the Brazilian Public Agricultural Research Corporation (EMBRAPA) and São Paulo State University (UNESP) have close links with a number of other research institutions, developing collaborative research projects for the divulgation of new technologies for corn production.…”
Section: Brazilian Research In Corn Productionmentioning
confidence: 99%
“…Araújo et al [4] investigated the collaborative public networks of corn research in Brazil between 2006 and 2010, and found close ties between the institutions involved in the enhancement of cultivars and those working on the development of technology for the improvement of productivity (Figure 1). Research efforts are concentrated in Southeast Brazil, where the Brazilian Public Agricultural Research Corporation (EMBRAPA) and São Paulo State University (UNESP) have close links with a number of other research institutions, developing collaborative research projects for the divulgation of new technologies for corn production.…”
Section: Brazilian Research In Corn Productionmentioning
confidence: 99%